Social Work Between Oppression and Emancipation. Histories of Discomfort and Inspiration in Europe. - Berteke Waaldijk (Social Work and Society)
Social workers who work with clients are used to asking about the past. They enquire about the personal history of the client. They try to find out how the problem their client deals with has developed. This allows them to 'start where the client is' In that sense an interest in history is a "˜natural' thing for social workers, just as all other professionals who deal with people they have to know and understand something about 'what happened until now'. History however is more than the individual facts that compose a person's past. History is also knowledge that goes beyond the individual; it describes how specific events can be understood in larger contexts of historical development. For social workers there are several ways in which knowledge about the past can be usefully expanded beyond understanding of the life-stories of individual clients.